Young men's accounts of living with oculocutaneous albinism in relation to identity and masculinity - Van der Walt, James Alexander (My University, 2018)
The current research arose from a particular interest in the ways in which different subgroups of men form and navigate their male identities and their masculinities. The decision to focus on the experiences of men living with oculocutaneous albinism stemmed from two inter-related premises: firstly, there is a dearth of research around this particular minority group; and secondly, there has been a call for the life experiences of this particular population to receive greater attention and understanding. Four participants were interviewed using a semi-structured interview schedule. The transcribed data gathered from these interviews was subject to a computer-aided thematic analysis. The findings of the current research suggest that the experiences of being stigmatized due to oculocutaneous albinism were highly injurious to the participants and lead them to internalize a strong sense of shame. This in turn affected the ways in which the participants experienced themselves in the world and interacted with others relationally, including in relation to friendships and more intimate partnerships. All of the participants feared that their albinism would make them less desirable to prospective life partners and were concerned that close others might be stigmatized by association with them. Their experiences appeared to influence the participants’ positioning of themselves in relation to other men and were also implicated in the complex nature of their racial identity. Participants demonstrated a capacity to be reflective about their life experiences and about the responses of others towards them in respect of their condition.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts (Clinical Psychology), 2018
Keywords: Men--South Africa--Identity; Adolescent psychology--South Africa; Identity (Psychology) in youth--South Africa; Masculinity--South Africa; Albinos and albinism--South Africa